Exploring the submarine geomorphology of Te Rua-o-te-Moko Fiordland, Aotearoa New Zealand - Unland, Ellen; Gorman, Andrew R.; Barnes, Philip M.; Moy, Christopher M.; Bowman, Hamish; Wilson, Gary S.; Forwick, Matthias; Hillman, Jess I. T. (Frontiers in Earth Science, 2025)
Temperate fjords serve as key environments for understanding glacial landscape evolution, sedimentary processes, and dynamics. These overdeepened, glacially carved inlets serve as high-resolution repositories of past climate and ice behaviour. While previous studies have highlighted the global significance of carbon trapping in temperate fjords, Te Rua-o-te-Moko Fiordland remains relatively understudied. This study provides a state-of-the-art overview of these fjords, integrating high-resolution bathymetry, marine seismic profiles, and topographic data to identify, discuss and assess spatial variability in fjord morphology. The results reveal a pronounced north-south gradient in geomorphic complexity. Northern fjords tend to be short, linear, and tectonically constrained, with narrow mouths and shallower basins. In contrast, southern fjords exhibit greater catchment areas, more complex geometries, deeper basins, and wider fjord mouths. These spatial variations reflect differences in glacial erosion efficiency, influenced by regional tectonics, bedrock lithology and catchment configuration. We identify widespread entrance sills, terminal moraines, and buried paleodeltas, suggesting episodic glacier retreat punctuated by stillstands. Overdeepened main basins show significant sediment infill, highlighting their potential as carbon sinks. The observed geomorphological patterns provide new insights into glacier dynamics, ice retreat mechanisms, and sediment depositional processes in a southern mid-latitude fjord setting. By establishing a spatial geomorphic framework of the fjords of Te Rua-o-te-Moko Fiordland, this study enhances our understanding of fjord development, controls on sediment transport, and the interplay between glacial, tectonic, and lithologic factors. These findings provide critical insights into fjord evolution, with implications for reconstructing past climates, glacial dynamics, and carbon burial potential.